Acute pancreatitis in a patient treated with imatinib and gefitinib. (June 2021) - Escudero-Vilaplana, Vicente; Collado-Borrell, Roberto; Villanueva-Bueno, Cristina; Álvarez, Rosa; Herranz, Ana; Sanjurjo, María
Introduction: Use of oral antineoplastic agents (OAAs) has increased significantly in recent years. OAAs currently represent 30-50% of all cancer treatments. Drug interactions are the most frequent drug-related problem affecting OAAs. We describe the case of a patient who presented acute pancreatitis, possibly induced by the concomitant use of imatinib and gefitinib. Case report: A female patient received imatinib and gefitinib for the treatment of chronic myeloid leukemia and lung adenocarcinoma, respectively. Liver function and pancreatic enzyme values gradually worsened after initiation of imatinib, and the patient was diagnosed with acute pancreatitis. Management and outcomes: Imatinib was discontinued owing to pancreatic toxicity. Gefitinib was subsequently discontinued owing to tumor progression. The patient received supportive measures for pancreatitis, although she eventually died 3 months after the onset of symptoms. Discussion: To our knowledge, this is the first case in the medical literature of acute pancreatitis possibly induced by an interaction between imatinib and gefitinib. The interaction most likely arose because imatinib is a CYP2D6 inhibitor and could therefore impair the metabolism of gefitinib (a CYP2D6 substrate) and increase its serum concentration. This interaction is extremely rare. However, due to its severity, hepatic and pancreatic function should be carefully monitored in patients treated with imatinib and/or gefitinib and other inhibitors or inducers of CYP2D6 and CYP3A4.